Let's denote the current age of the girl as \( g \) and the current age of the old lady as \( l \).
From the problem, we have the following two relationships:
-
The old lady is currently 5 times as old as the girl: \[ l = 5g \]
-
Six years ago, the old lady was 8 times as old as the girl: \[ l - 6 = 8(g - 6) \]
Now let's substitute the first equation into the second equation:
Substituting \( l \) into the second equation gives: \[ 5g - 6 = 8(g - 6) \]
Expanding the right side: \[ 5g - 6 = 8g - 48 \]
Now, let's rearrange the equation to isolate \( g \): \[ 5g - 8g = -48 + 6 \] \[ -3g = -42 \] \[ g = 14 \]
Now that we have the age of the girl, we can find the age of the old lady using the first equation: \[ l = 5g = 5 \times 14 = 70 \]
So the current ages are:
- The girl is 14 years old.
- The old lady is 70 years old.